2019
DOI: 10.1002/bin.1655
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing conditions for recognizing pictures of family members in a patient with Alzheimer's disease

Abstract: In the present study, an 89-year-old woman with the neurocognitive disorder Alzheimer's disease participated.The purpose was to study recognition of the participant's relatives' faces with the use of sorting tests and matchingto-sample (MTS) trainings and tests for emergent relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Among the different types of apparatus used for applied research, researchers used the computer most often at 43.86% ( n = 50) of the 114 apparatuses that were used within the 100 applied studies that were included in the current review. Studies that used computers primarily utilized programmable software such as Microsoft’s Visual Basic (e.g., Lovett & Rehfeldt, 2014; Varella & de Souza, 2015); preprogrammed computer software that collected the DV automatically (e.g., Headsprout Early Learning for Grindle et al, 2013; a custom match-to-sample program for Brogård-Antonsen & Arntzen, 2019); or applications that run on mobile devices (e.g., Motiv8 for Martner & Dallery, 2019; Plickers for Radley et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Among the different types of apparatus used for applied research, researchers used the computer most often at 43.86% ( n = 50) of the 114 apparatuses that were used within the 100 applied studies that were included in the current review. Studies that used computers primarily utilized programmable software such as Microsoft’s Visual Basic (e.g., Lovett & Rehfeldt, 2014; Varella & de Souza, 2015); preprogrammed computer software that collected the DV automatically (e.g., Headsprout Early Learning for Grindle et al, 2013; a custom match-to-sample program for Brogård-Antonsen & Arntzen, 2019); or applications that run on mobile devices (e.g., Motiv8 for Martner & Dallery, 2019; Plickers for Radley et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To assess for generalization of the MTS-training, it would be of interest to study how participants with dementia respond when presented novel stimuli in an identity matching test after the MTS-training and test (see, Camara et al, 2017;Steingrimsdottir & Arntzen, 2011a). Furthermore, it is important to replicate earlier studies which have employed MTS training and tests with longer delays (Steingrimsdottir & Arntzen 2011b), and showed maintenance of matching performance over time (Brogård-Antonsen & Arntzen, 2019). In sum, the studies suggested above would gain more knowledge about the use of the MTS-procedure to detect behavioral changes related to the progression of the disease.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Remembering can be described as emitting a correct response to a comparison stimulus after a temporal delay between the offset of a sample stimulus and the onset of the comparison stimuli (White, 2013). The MTS procedure has been used to assess the progression of dementia (Fowler, Saling, Conway, Semple, & Louis, 1995), and in maintaining and retraining functional skills (Brogård-Antonsen & Arntzen, 2019;Cowley, Green, & Braunling-McMorrow, 1992;Ducatti & Schmidt, 2016;Steingrimsdottir & Arntzen, 2014).…”
mentioning
confidence: 99%
“…However, the equivalence theory can be used in teaching new concepts to normal children and adults, including college students (Sidman et al, 1986;Hove, 2003;Saunders et al, 2005;Fienup et al, 2010;Walker et al, 2010;Lovett et al, 2011;Grisante et al, 2013;Placeres, 2014;Fienup et al, 2015). Some neurocognitive disorders, like Alzheimer's disease, are also a research area that equivalence theory deals with where it is discussed that derived relational responding is deteriorated as the cognitive impairment advances over time (Bódi et al, 2009;Gallagher & Keenan, 2009;Steingrimsdottir & Arntzen, 2011;Sidman, 2013;Arntzen et al, 2013;Arntzen & Steingrimsdottir, 2014;Seefeldt, 2015;Ducatti & Schmidt, 2016;Arntzen & Steingrimsdottir, 2017;Brogård-Antonsen & Arntzen, 2019).…”
Section: Introductionmentioning
confidence: 99%